2015
DOI: 10.1021/acs.jmedchem.5b01303
|View full text |Cite
|
Sign up to set email alerts
|

Novel Electrophilic and Photoaffinity Covalent Probes for Mapping the Cannabinoid 1 Receptor Allosteric Site(s)

Abstract: Undesirable side effects associated with orthosteric agonists/antagonists of cannabinoid 1 receptor (CB1R), a tractable target for treating several pathologies affecting humans, have greatly limited their translational potential. Recent discovery of CB1R negative allosteric modulators (NAMs) has renewed interest in CB1R by offering a potentially safer therapeutic avenue. To elucidate the CB1R allosteric binding motif and thereby facilitate rational drug discovery, we report the synthesis and biochemical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 71 publications
3
66
0
1
Order By: Relevance
“…Since the discovery of PSNCBAM-1, some SAR studies 3537 showed that CB1R allosteric modulators with improved affinity, efficacy and potency, could be generated from PSNCBAM-1 template. With the aim to extend the knowledge about the structural requirements of PSNCBAM-1 template as CB1R allosteric modulator, in this work we studied some derivatives designed by introducing various modifications on PSNCBAM-1 structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of PSNCBAM-1, some SAR studies 3537 showed that CB1R allosteric modulators with improved affinity, efficacy and potency, could be generated from PSNCBAM-1 template. With the aim to extend the knowledge about the structural requirements of PSNCBAM-1 template as CB1R allosteric modulator, in this work we studied some derivatives designed by introducing various modifications on PSNCBAM-1 structure.…”
Section: Resultsmentioning
confidence: 99%
“…In an in vivo study of acute feeding model, PSNCBAM-1 showed to decrease food intake and body weight. 27 Several analogs of PSNCBAM-1 3537 have been reported and structure-activity relationship studies showed that alkyl substitution at the 2-aminopyridine moiety is important for CB1R allosteric modulation; in particular, tertiary amine substitution is more favorable than secondary. Furthermore, the 4-position on the phenyl group tolerates structural modifications, but electron-withdrawing groups such as cyano or CF 3 are preferred, 35 and the substitution of the urea group with other spacers such as carbamate, methylated ureas or cyclic ureas, reduces the activity.…”
Section: Introductionmentioning
confidence: 99%
“…4-(Ethoxycarbonyl)phenyl-substituted thiourea 9b gave the excepted 2-[4-(ethoxycarbonyl)phenylimino]-1,3-thiazino [5,6-b]indole-4-one (11) in good yield upon treatment with the bromide reagent applied above. For 3,4,5-trimethoxyphenyl-substituted 9c, the preferable reaction path in the Hugerschoff reaction was the formation of thiazole ring system 2-(indol-2-carbonylamino)-5,6,7-trimethoxy-benzothiazole (12). …”
Section: Resultsmentioning
confidence: 99%
“…The crystalline residues were triturated with acetone (9a-c), filtered off and purified as indicated. (12). To an intensively stirred suspension of thiourea derivatives 9a-c (0.7 mmol) in dichloromethane (20 mL), phenyltrimethylammonium tribromide (0.26 g, 0.69 mmol) was added in one portion at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation